Pengaruh Liquidity dan Leverage Terhadap Firm Performance Dengan Firm Size Sebagai Variabel Moderasi - Tang, Sukiantono (E-Jurnal Akuntansi, 2022)
Firm performance is a description of the company's condition and ability in the past and current period to be evaluated. The purpose of the study was to obtain empirical evidence of the effect of liquidity and leverage on firm performance with firm size as a moderating variable. The study was conducted on companies listed on the Indonesia Stock Exchange for the period 2017-2021. The research sample was 2,033 observations. The data were processed by multiple linear regression and moderated regression analysis. The results of liquidity research have a positive effect on firm performance with firm size moderation. Leverage has no effect on firm performance. Keywords: Liquidity, Leverage, Firm Performance, Firm Size.